Perceptions about the Unified Health System among users and health professionals in the city of Santa Cruz-RN - Gleiciane da Silva Fonseca; Tayssa Suelen Cordeiro Paulino; Ildone Forte de Morais; Cecília Nogueira Valença; Raimunda Medeiros Germano (Universidade de Fortaleza, 2012)
Objective: To evaluate the level of knowledge of users and health professionals on the Unified Health System (UHS), highlighting the prospects for enhancing citizen participation in health policy. Methods: A descriptive and exploratory study with a qualitative approach, developed between April and July 2010 through semi-structured interviews with 23 people, among them four health professionals, and 19 users, who lived in an area of the Family Health Strategy city of Santa Cruz, RN, Brazil. The collected data were analyzed using thematic analysis, one of the modalities of content analysis, through the stages of reading and exploration of material, creating categories and linking them with theoretical references. Results: The survey showed that there are differences between the knowledge of users and health professionals, because while these critiques cited based on the principles of UHS legally established, users demonstrated ignore the UHS, conceptualizing it as the National Health Card . The speeches of the participants pointed to difficulties in access to health and a lack of educational activities in health, which can make difficult to develop democratic practices in this sector policies. Conclusions: The UHS was a breakthrough in health care in Brazil, but there are still barriers to the consolidation of a universal, integrated and equanimous. From this perspective, to contribute to the realization of the public health system, stands out importance of unity of diverse social actors (educators, managers and health professionals), as well as health education for the strengthening of popular participation.